The Appropriateness of the Length of Insulin Needles Based on Determination of Skin and Subcutaneous Fat Thickness in the Abdomen and Upper Arm in Patients with Type 2 Diabetes - Sim, Kang Hee; Hwang, Moon Sook; Kim, Sun Young; Lee, Hye Mi; Chang, Ji Yeun; Lee, Moon Kyu (Diabetes & metabolism journal, 2014)
Longer needle and complicated insulin injection technique such as injecting at a 45-degree angle and making skinfolds may decrease patient compliance to insulin injection therapy. In this light, shorter insulin needles have been recently developed. However, it is necessary to ascertain that such shorter needles are appropriate for Korean patients with diabetes as well. First, the diverse demographic and diabetic features of 156 Korean adults with diabetes were collected by a questionnaire and a device unit of body fat measurement. The skin and subcutaneous fat thicknesses of each subject were measured by Ultrasound device with a 7- to 12-MHz probe. Data were analyzed using analysis of variance and multiple linear regression. The mean skin thickness was 2.29±0.37 mm in the abdomen and 2.00±0.34 mm in the upper arms, and the mean subcutaneous fat thickness was to 10.15±6.54 mm in the abdomen and 5.50±2.68 mm in the upper arms. Our analysis showed that the factors affecting the skin thickness of the abdomen and upper arms were gender and body mass index (BMI), whereas the factors influencing the subcutaneous fat thickness in the abdomen were gender and BMI, and the factors influencing the subcutaneous fat thickness in the upper arms were gender, BMI, and age. Insulin fluids may not appear to be intradermally injected into the abdomen and upper arms at any needle lengths. The risk of intramuscular injection is likely to increase with longer insulin needles and lower BMI. It is recommended to fully inform the patients about the lengths of needles for insulin injections. As for the recommended needle length, the findings of this study indicate that needles as short as 4 mm are sufficient to deliver insulin for Korean patients with diabetes.